MTHFD1 formyltetrahydrofolate synthetase deficiency, a model for the MTHFD1 R653Q variant, leads to congenital heart defects in mice. Issue 12 (26th September 2015) - Christensen, Karen E.; Deng, Liyuan; Bahous, Renata H.; Jerome‐Majewska, Loydie A.; Rozen, Rima
Abstract : Background: A single nucleotide polymorphism (SNP) in the synthetase domain of the trifunctional folate‐dependent enzyme MTHFD1 (c.1958G>A, R653Q) has been linked to adverse pregnancy outcomes, neural tube defects, and possibly congenital heart defects. Maternal folate deficiency may also modify the risk associated with these disorders. We recently established a mouse model with a mild deficiency of 10‐formyltetrahydrofolate synthetase activity in MTHFD1 ( Mthfd1S +/− mice) to investigate disorders associated with SNPs in this gene. The effect of synthetase deficiency on embryonic heart development has not yet been examined. Methods: Female Mthfd1S +/+ and +/‐ mice were placed on control and folate‐deficient diets for 6 weeks before mating to Mthfd1S +/‐ males. Embryos and placentae were collected at embryonic day 14.5. Embryos were evaluated for congenital heart defects by histological examination. Results: Embryonic Mthfd1S +/‐ genotype was associated with an increased incidence of heart defects, primarily ventricular septal defects. Other markers of embryonic development (crown‐rump length, embryonic weight, embryonic delay, placental weight, and thickness of the ventricular myocardium) were not affected by embryonic genotype. Maternal genotype and diet did not have a significant effect on these outcomes. Conclusion: Deficiency of the MTHFD1 10‐formyltetrahydrofolate synthetase activity in embryos is associated with increased incidence of congenital heart defects. Birth Defects Research (Part A) 103:1031–1038, 2015. © 2015 Wiley Periodicals, Inc.